Digital Platform's: Investigations in the Application of Music Practice Learning - Dani Nur Saputra (Ahlimedia Press, 2021)
One of the competencies that must be possessed in the 21st century is digital literacy skills. This ability must be possessed by every student and lecturer in integrating digital platforms into learning, especially in the current pandemic era. This study aims to investigate the effectiveness of a digital platform in its application to practical courses. Researchers use google classroom as a sample of the many types of digital platforms. This type of research is descriptive qualitative using a case study approach. The object of this research were 26 active students who took music ensemble courses, while the variable being investigated was the use of google classroom in learning. Data collection was carried out by means of questionnaires, observations, and interviews. The results show that digital platforms can be used as an alternative solution to carry out online learning in the midst of a pandemic. However, it is not optimal for the music ensemble course because of several factors, including the location of the student's residence which is difficult to get a signal, material that students find difficult, the availability of their own musical instruments, and the student's ability to play music.